TEAM LEARNING IN A LEARNING ORGANIZATION: THE PRACTICES OF TEAM LEARNING AMONG UNIVERSITY LIBRARIANS IN MALAYSIA - Ahmad Kassim, Norliya; Mohd. Nor, Azizah (Malaysian Journal of Library and Information Science, 2017)
This paper reports a part of an investigation on learning organization and organizational learning practices at university libraries in the Klang Valley of Malaysia. The study aimed to find out whether or not academic librarians are applying the concepts and practices of learning organization at three levels, namely individual level, team level and the organizational level. This paper focuses on the perceptions of academic librarians on the practices of team level learning in public and private university libraries. There are 17 variables on team level learning that formed a part of a survey instrument using a seven-point interval scale. The instrument was distributed to a total population of 250 librarians of the public and private university libraries in the Klang Valley of Malaysia. A total of 191 (76.4%) respondents returned the questionnaire. The study found that academic librarians perceived learning at the team level does exist in general, but they were not overly convinced of the extent to which the practices exist. The results of the Mann-Whitney U test showed that there is a statistical significant difference in the perceptions of team level learning practices between the senior and middle level academic librarians implying that the senior level librarians had more positive perceptions on the practices of team level learning in their organizations than the middle level librarians.